Using learning analytics to redesign core pedagogy subjects: a case in point. Issue 2 (7th February 2022) - Eady, Michelle J.; Green, Corinne A.; Fulcher, David; Boniface, Tim
ABSTRACT: Research has demonstrated a correlation between lecture attendance and students' academic achievement. However, students may not attend lectures for a variety of reasons. The provision of lecture recordings online can also negatively impact lecture attendance and student achievement. These facts implore us to be courageous and explore new approaches to improve and expand learning experiences. This paper describes how a diverse team of academics, learning analytics and education design staff at [the University of Wollongong] came together to explore this issue and develop an approach that could better support the learning of our students resulting in higher rates of achievement while adapting to students' needs for flexibility and connection. Details are given regarding the analysis of learning analytics data, and how these data have informed and directed a transformed learning design for a core undergraduate subject in the field of teacher education.